From growth and fixed creative mindsets to creative thinking: an investigation of the mediating role of creativity motivation - He, Wu-jing; Chiang, Tin-wai (Frontiers in Psychology, 2024)
Studies documenting and seeking to understand the mindset effect have yielded mixed and inconclusive findings. The present study sought to address the research question pertaining to the mindset effect on creative thinking and its underlying mechanism from the perspectives of social cognitive theory and mindset theory, which postulate a motivational mechanism underlying the mindset-creativity link. Specifically, the study aimed to examine the mediating role of creativity motivation in the effects of growth and fixed creative mindsets on creative thinking. A convenience sample of 948 (52.1% females) college students from three universities in Hong Kong participated in the study. Creative mindset, creativity motivation, and creative thinking were assessed using the Chinese version of the Creative Mindset Scale, the Creativity Motivation Scale, and the Test for Creative Thinking-Drawing Production (TCT-DP), respectively. Lending support to the perspectives of social cognitive and mindset theories, the results of mediation analyses conducted using Preacher and Hayes's (2008) bootstrapping approach indicated that creativity motivation had partially mediating effects on the positive and negative roles of growth and fixed mindsets, respectively, in creative thinking.Enriching the research on the motivation mechanism underlying the impacts of creative mindsets on creative thinking, the results further illustrated that creativity motivation has a stronger mediating effect on the impact of growth creative mindset on creative thinking than on that of fixed creative mindset. The possible theoretical and educational implications of the findings of this research are discussed.